Über die Hindernisse und die Unterscheidungen der Schnittflächen im zweimaligen Faserraume - Matuzevičius, A. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Матузявичюс, О препятствиях и различающих секущих поверхностей двукратного расслоенияA. Matuzevičius, Apie kertamųjų paviršių kliūtis ir skiriamąsias dvigubuose sluoksniavimuose